Lines of courage - Nielsen, Jennifer A. (Scholastic Press, an imprint of Scholastic Inc., 2022)
From the assassination that triggers World War I in 1914 to Armistice Day in 1918, the story follows the fates of five young people on both sides of the conflict--each facing their portion of the war with courage, until the end of the war brings them together. Includes information on the history of the war.